Melatonin Application to Pisum sativum L. Seeds Positively Influences the Function of the Photosynthetic Apparatus in Growing Seedlings during Paraquat-Induced Oxidative Stress - Szafrańska, Katarzyna; Reiter, Russel J.; Posmyk, Małgorzata M. (Frontiers in Plant Science, 2016)
Melatonin, due to its pleiotropic effects plays an important role improving tolerance to stresses. Plants increase endogenous melatonin synthesis when faced with harsh environments as well as exogenously applied melatonin limits stress injuries. Presented work demonstrated that single melatonin application into the seeds during pre-sowing priming improved oxidative stress tolerance of growing seedlings exposed to paraquat (PQ). PQ is a powerful herbicide which blocks the process of photosynthesis under light conditions due to free radicals excess production, when O2 is rapidly converted to O2•– and subsequently to other reactive oxygen species. The parameters of chlorophyll fluorescence [Fv/Fm, Fv/Fo, Rfd, ΦPSII, qP, and non-photochemical quenching (NPQ)] in all variants of pea leaves (derived from control non-treated seeds – C, and those hydroprimed with water – H, and hydroprimed with melatonin water solution 50 or 200 μM – H-MEL50 and H-MEL200, respectively) were analyzed as a tool for photosynthetic efficacy testing. Moreover stability of the photosynthetic pigments (chlorophylls a, b, and carotenoids) was also monitored under oxidative stress conditions. The results suggest that melatonin applied into the seed significantly enhances oxidative stress tolerance in growing seedlings. This beneficial effect was reflected in reduced accumulation of O2•– in leaf tissues, preservation of photosynthetic pigments, improved functioning of the photosynthetic apparatus and higher water content in the tissues during PQ-mediated stress. Our findings provide evidence for the physiological role of this molecule and serve as a platform for its possible applications in agricultural or related areas of research.